Učinkovitost uporabe elastičnih lepilnih trakov (kinesio taping) - Zalar, Metka (Rehabilitacija (Ljubljana), 2011)
After the Olympic Games in Beijing in 2008, kinesio taping has spread widely all over the world. This therapeutic procedure is used in combination with other terapeutic procedures in the treatment of various musculosceletal and neuromuscular disorders. The purpose of this article was to examine a variety of studies examining the effectiveness of kinesio taping. The articles were retrieved from scientific journals and web pages. The article reviews 18 studies. Opinions of the authors about the effectiveness of kinesio taping differ. It would be necessary to carry out more randomised studies to confirm the effectiveness of kinesio taping.
Keywords: efficiency; elastični lepilni trakovi; therapy; učinkovitost; zdravljenje